2011
DOI: 10.1093/hmg/ddr048
|View full text |Cite
|
Sign up to set email alerts
|

Broad activation of the ubiquitin–proteasome system by Parkin is critical for mitophagy

Abstract: Parkin, an E3 ubiquitin ligase implicated in Parkinson's disease, promotes degradation of dysfunctional mitochondria by autophagy. Using proteomic and cellular approaches, we show that upon translocation to mitochondria, Parkin activates the ubiquitin–proteasome system (UPS) for widespread degradation of outer membrane proteins. This is evidenced by an increase in K48-linked polyubiquitin on mitochondria, recruitment of the 26S proteasome and rapid degradation of multiple outer membrane proteins. The degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
935
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 883 publications
(990 citation statements)
references
References 42 publications
43
935
11
1
Order By: Relevance
“…These data suggest that PINK1 and Parkin induce the ubiquitination of VDAC1 to recruit the autophagic components p62 and HDAC6 for the specific turnover of damaged mitochondria. However, other studies report that p62 and VDAC1 are dispensable for Parkin-induced mitophagy (Narendra et al, 2010b; and that the outer membrane protein degradation caused by the ubiquitin -proteasome system is critical for Parkin-mediated mitophagy (Chan et al, 2011). We expect that more important details of the molecular mechanism of mitophagy mediated by the PINK1 -Parkin pathway will be revealed soon.…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 90%
“…These data suggest that PINK1 and Parkin induce the ubiquitination of VDAC1 to recruit the autophagic components p62 and HDAC6 for the specific turnover of damaged mitochondria. However, other studies report that p62 and VDAC1 are dispensable for Parkin-induced mitophagy (Narendra et al, 2010b; and that the outer membrane protein degradation caused by the ubiquitin -proteasome system is critical for Parkin-mediated mitophagy (Chan et al, 2011). We expect that more important details of the molecular mechanism of mitophagy mediated by the PINK1 -Parkin pathway will be revealed soon.…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 90%
“…However, although loss of Mitofusin is necessary for mitophagy to proceed, it is not by itself sufficient to trigger mitophagy and PINK1 and Parkin can initiate mitophagy in cells lacking Mitofusin. 56,68 Mitochondrial fragmentation in the absence of Mitofusin thus appears to be a permissive rather than a triggering event.…”
Section: The Pink1/parkin Pathway Of Mitophagymentioning
confidence: 99%
“…In support of this model, inhibition of proteosome activity prevents mitophagy of damaged mitochondria. 56,68 A proteomic study in HeLa cells revealed Parkin-and proteosome-dependent degradation of Miro, Mitofusin, hFis1, and Tom70, as well as others, before mitophagy. However, as mentioned above, while proteosomal elimination of Mitofusin is required, it is not sufficient for initiation of mitophagy.…”
Section: Parkin Promotes Ubiquitination Of Mitochondrial Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Parkin has been shown to target some mitochondrial proteins for proteasomal degradation independently of mitophagy 37,38 . Therefore, multiple approaches should be used, at least in initial experiments, to verify the method is functional.…”
Section: Assessment Of Mitophagymentioning
confidence: 99%